Vertical transmission and clinical outcome of the neonates born to SARS-CoV-2-positive mothers: a tertiary care hospital-based observational study - Arun Prasad; Pradeep Kumar; Lokesh Kumar Tiwari; Fadila; Ambrin Akhtar; Bhabesh Kant Chaudhary; Neha Chaudhry (BMJ Publishing Group, 2021)
Background Neonatal transmission of SARS-CoV-2 from positive mothers to their babies has been a real concern, opening the arena of research in this area.Objective To detect the possibility of vertical transmission of SARS-CoV-2 from COVID-19-positive mothers to their neonates and the clinicopathological outcome in them.Design A single-centre, prospective, observational study involving 47 COVID-19-positive mothers and their neonates.Setting A tertiary care hospital in Eastern India.Participants Neonates born to SARS-CoV-2-infected mothers.Main outcome measures We investigated the SARS-CoV-2 positivity rate by real-time reverse transcriptase-PCR (RT-PCR) done twice (on admission and after 24 hours of admission) in neonates born to SARS-CoV-2-positive mothers, who tested RT-PCR positive for this virus in their nasopharyngeal swab. Clinical outcome was also assessed in these neonates during their hospital stay.Results Out of 47 neonates born to SARS-CoV-2-positive mothers, four were SARS-CoV-2 positive by RT-PCR. All the neonates in our study were discharged home in stable condition after management of acute complications. None of them required readmission.Conclusion Vertical transmission occurs in neonates born to COVID-19-positive mothers; however, the risk is small. Majority of the neonates remain asymptomatic with good clinical outcome.